A CASE OF SENSONEURAL HEARING LOSS MANAGED WITH HOMOEOPATHIC SIMILIMUM- AN EVIDENCE BASED CASE REPORT (AYUSHDHARA, 2020)
Sensoneural hearing loss (SNHL) is most common form of hearing loss world-wide. SNHL results from lesions of the cochlea, 8th nerve and central auditory pathways. The causes of SNHL may be congenital, traumatic, infectious, inflammatory, iatrogenic, neoplastic and senile. The development of drugs to treat or prevent SNHL has proven challenging. In modern system of medicine this disease is difficult to treat as treatment is directed towards cause only. Rehabilitation with hearing aids and other devices are also necessary for management of such cases. This article is about a patient of 73 years of age, who was suffering from senile SNHL and improved with homoeopathic medicine, Baryta carb 200, and without need of hearing aid device.